1996
DOI: 10.1051/aas:1996199
|View full text |Cite
|
Sign up to set email alerts
|

Variable stars in the field of the old open cluster NGC 2243

Abstract: Abstract. -We report results of photometric monitoring of the NGC 2243 field in V and I filters. Two W UMatype systems and three detached eclipsing binaries were discovered. Both contact systems are likely members of the cluster. One of the detached binaries -variable V1 -has a period P=1.188 day. This variable is located at the cluster's turnoff in the color-magnitude diagram. Determination of parameters for components of V1 can provide direct information about properties of turnoff stars in NGC 2243 as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 14 publications
(19 reference statements)
11
64
0
Order By: Relevance
“…Instead the effect on the [Ca/Fe] ratio is negligible. Our temperature scale is consistent with that of Kaluzny et al (1996); this is not surprising given the adoption of the same photometry and reddening. Figure 6 shows the position of the stars on a T eff − V space, similar to a color magnitude diagram.…”
Section: Error Estimatessupporting
confidence: 77%
See 3 more Smart Citations
“…Instead the effect on the [Ca/Fe] ratio is negligible. Our temperature scale is consistent with that of Kaluzny et al (1996); this is not surprising given the adoption of the same photometry and reddening. Figure 6 shows the position of the stars on a T eff − V space, similar to a color magnitude diagram.…”
Section: Error Estimatessupporting
confidence: 77%
“…Gratton & Contarini (1994) confirmed this low metallicity using high-resolution spectra. They determined the iron abundance in two giants of the cluster and found Kaluzny et al (1996) found E(V − I) = 0.10 ± 0.04. Kaluzny et al (2006) extended their study of NGC 2243 to the analysis of detached eclipsing binaries.…”
Section: Ngc 2243: An Old Metal-poor Open Clustermentioning
confidence: 99%
See 2 more Smart Citations
“…There are some indications that the Friel et al (2002) [ Fe/ H ] References.-Galactic coordinates, reddenings, and distances for globular clusters are from Harris (1996); Galactic coordinates, reddenings, and distances for open clusters are from Friel et al (2002). Sources for photometry: (1) Kaluzny et al 1998; (2) Piotto et al 2002;(3) Feltzing & Gilmore 2000;(4) Chaboyer et al 2000;(5) this paper; (6) Kaluzny 1988; (7) Carraro et al 2001;(8) Kassis et al 1997;(9) Bergbusch et al 1991;(10) Anthony-Twarog et al 1990;(11) Kim et al 2001;(12) Sandquist 2004;(13) Stetson et al 2003;(14) Kalirai et al 2001;(15) Andreuzzi et al 2004;(16) Durgapal et al 2001;(17) Tosi et al 1998;(18) Guetter 1993;(19) Kaluzny & Mazur 1991;(20) Gozzoli et al 1996. All OC photometry was obtained from WEBDA, maintained by J.-C. Mermilliod ( http:// obswww.unige.ch /webda /navigation.html).…”
Section: Discussionmentioning
confidence: 98%